Diversification and desynchronicity: An organizational portfolio perspective on corporate risk reduction - Xue-Feng Shao; Kōstas Iō. Guliamos; Ben Nan-Feng Luo; Shigeyuki Hamori; Stephen Satchell; Xiao-Guang Yue; Jane XJ Qiu (Risks, 2020)
A longstanding objective of managers is to reduce risk to their businesses. The conventional strategy for risk reduction is diversification; however, evidence for the effectiveness of diversification remains inconclusive. According to Organizational Portfolio Analysis, firms are viewed as portfolios of business units, and the key to risk reduction is both diversification and synchronization compensation. This study introduces 'desynchronicity', a process that operationalizes synchronization compensation by assessing the degree of correlation between income streams of business units. Two samples of 737 and 332 firms (from COMPUSTAT) were used to empirically test the relationships between diversification and risk, and desynchronicity and risk. The results show that diversification alone will not always lead to a lower corporate risk. To reduce risk, firms also need to consider the desynchronicity of their business portfolios. Other practical implications include improved decisions on portfolio composition.
Keywords: 330; risk reduction determinants; product diversification; synchronization compensation; improved portfolio decisions